The instrumentation and initial analysis of the short-term control and stability derivatives of an ASK-I3 glider - Browne, Keith R.J. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2004. 220 leaves single printed pages ,preliminary pages i-xiv and numberd pages 1-188.Includes bibliography.list of figures and used a Hp Scanjet 8250 Scanner to pdf format (OCR),